Assessment of the pathogenicity of marine Cladosporium spp. towards mangroves. Issue 2 (30th November 2016) - Liu, Y.; Li, Y.; Lin, Q.; Zhang, Y.
Summary: Mangroves play an important role in coastal ecosystems. In this work, Cladosporium spp were isolated from a natural mangrove environment in Zhanjiang Bay, Guangdong Province, China. Ninety‐one isolates were obtained and identified as Cladosporium cladosporioides, C. colocasiae, C. oxysporum, C. perangustum, C. sphaerospermum, C. tenuissimum and C. uredinicola . Forty‐two isolates were selected and tested for pathogenicity towards mangroves. The results showed that pathogenic isolates were found on Avicennia marina, Kandelia candel and Rhizophora stylosa with prevalence of 93.40%, 83.52% and 7.41%, respectively. This indicated that A. marina and K. candel were more vulnerable to Cladosporium ssp. than R. stylosa . Among the seven species, C. colocasiae had the strongest pathogenic effect towards A. marina and K. candel with a prevalence of 100.00%. The rest of the seven species also showed pathogenic effects on the same plants. These results provided valuable insights into the effect of various pathogens on mangroves.